GE_GERICHTE A/2604/2019 vom 17. Oktober 2019 - GE Cour de justice (2019)
CONTINUATION DE LA POURSUITE; DECISION DE MAINLEVEE; SAISIE IMMOBILIERE; REQUISITION DE VENTE | LP.79.al1; LPGA.49; LPGA.54.al1.leta; LP.102.al2; LAMal.64a; LP.20a.al2.ch5